ADHD: Beyond Core Symptoms and Specialist Care - Rafał R. Jaeschke (Journal of Clinical Medicine, 2026)
Attention-deficit/hyperactivity disorder (ADHD) is still too often regarded as a marginal or highly specialist concern, rather than as a condition with direct relevance to everyday clinical practice [...]